Time-kill assay of pomegranate (Punica granatum L) seed ethanolic extract against streptococcus sanguis; the cause of recurrent aphthous stomatitis - Riani Setiadhi; Irna Sufiawati; Dewi Zakiawati; Dani R. Firman (DiscoverSys Inc., 2018)
Objective: To examine the antimicrobial activity of pomegranate seed using a time-kill-assay by measuring the number of bacteria left at a various time points after exposure to the substance.Material and Methods: Pomegranate seeds were extracted by a maceration method using 70% ethanol as the solvent. The extract was evaluated for minimum inhibitory concentration and minimum bactericidal concentration against streptococcus sanguis ATCC 10556, using a microdilution method. The concentration used in time-kill-assay were 2 to 4 times MBC value and 48 hours incubation time as the initial value. Correlation of the concentration and time duration using semi-log graph, i.e. the x-axis as time duration with variation interval of 30, 60 and 90-seconds.Â Y-axis is the logarithmic value of the bacterial colonies number.Results: Bacteriostatic effect was observed at 4000 ppm concentration at 30, 60 and 90-seconds time intervals. The bactericidal effect was observed at 8000 ppm of concentration at the 90-second time interval, whereas 30 and 60-seconds remained bacteriostatic.Conclusion: The pomegranate seeds ethanolic extract is considered as antibacterial with a concentration-dependent category.